A Prosopographical Study of the ỉmʒ-ʿ Title Holders down to the End of the Old Kingdom: Part 2 – Corpus - León, Daniel González (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
The first part of this paper was published in the second issue of ZÄS 148 (2021). The sources of the ỉmʒ-ʿ title were presented in order to examine their nature, their provenance, and the social and historical context of the title’s holder. This second part contains the actual prosopographical list consisting of 37 entries, namely the documentation which supports the contents of Part 1.